2018
DOI: 10.3390/ani8010014
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study in Citizen Science: The Effectiveness of a Trap-Neuter-Return Program in a Chicago Neighborhood

Abstract: Simple SummaryStrong public support in the United States for the non-lethal management of free-roaming cats has prompted an increase in the practice of trap-neuter-return (TNR) over the past quarter-century, yet a paucity of analyzable data exists. Data sets collected by citizen scientists are likely to play an important role in filling this information void. A citizen scientist in Chicago, Illinois, recorded significant reductions in a free-roaming cat population as the result of a neighborhood TNR program. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 24 publications
7
72
1
Order By: Relevance
“…As has been noted elsewhere [ 42 , 45 ], the limitations of the present study include those invariably encountered when conducting a retrospective investigation, which is bound by the parameters and precision of the available data. Results for metrics tracked specifically as part of the three-year CCP (e.g., feline intake and euthanasia, and sterilization surgeries) were calculated for 12-month periods that correspond to the beginning (April) and ending (March) months of the program; results customarily tracked by AAWD, apart from the CCP, were based upon the calendar year.…”
Section: Study Limitationsmentioning
confidence: 97%
“…As has been noted elsewhere [ 42 , 45 ], the limitations of the present study include those invariably encountered when conducting a retrospective investigation, which is bound by the parameters and precision of the available data. Results for metrics tracked specifically as part of the three-year CCP (e.g., feline intake and euthanasia, and sterilization surgeries) were calculated for 12-month periods that correspond to the beginning (April) and ending (March) months of the program; results customarily tracked by AAWD, apart from the CCP, were based upon the calendar year.…”
Section: Study Limitationsmentioning
confidence: 97%
“…All articles focusing on free-roaming cats included a form of trap-neuter-return, as either the only method or one of the methods of cat population management, and, therefore, TNR appears to be the most widely accepted, or at least the most widely reported, non-lethal cat population management practice, though it is variable in delivery. Collectively, these TNR studies report varying degrees of success in controlling cat populations, with little to no effect on free-roaming cat populations reported in the short-term TNR programs in urban NYC [21] or rural Quebec [23], whereas the longer term (9-20 years) studies (n = 4) demonstrated significant decreases in free-roaming cat populations in rural and urban areas of the USA and Australia of between 54% and 100% [25][26][27][28]. However, all four long-term TNR programs were supplemented with removal (TR); mainly adoption/rehoming of social cats and the euthanasia of cats that tested positive to FeLV or FIV (feline leukemia and feline immunodeficiency virus respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Four articles assessed the impact of long-term conventional TNR programs on free-roaming cat populations in the United States [25][26][27], and in Australia [28], over extended periods of time; 23, 15, 10 and 9 years respectively. A US study [25] retrospectively evaluated a 23-year TNR program through census data collected before and during the program (program is ongoing).…”
Section: Long-term Tnr Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our point in relation to these studies and to others claiming population reductions following TNR remains that a large component of claimed reductions is removal of cats by adoption, euthanasia, migration, or death in situ. For example, of the 195 cats in one program, 59 were adopted, 67 disappeared, six were euthanised, three were returned to their owners, 13 died from other causes, two were relocated and one was seized [52]. In the ORCAT study in Florida, USA, 1111 cats were returned, but 1419 were removed by adoption, transfer to an adoption centre, euthanasia, death in care or dead on arrival [28].…”
Section: Tnr Will Reduce Urban Cat Populationsmentioning
confidence: 99%